Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

Constraints on mineral-associated and particulate organic carbon response to regenerative management: carbon inputs and saturation deficit - Alison E. King; Joseph P. Amsili; S. Carolina Córdova; Steve Culman; Steven J. Fonte; James Kotcon; Michael D. Masters; Kent McVay; Daniel C. Olk; Aaron M. Prairie; Meagan Schipanski; Sharon K. Schneider; et al. (Soil and Tillage Research, 2024)

The contribution of natural burials to soil ecosystem services: Review and emergent research questions - M. Pawlett; N.T. Girkin; L. Deeks; D.L. Evans; R. Sakrabani; P. Masters; K. Garnett; N. Márquez-Grant (Applied Soil Ecology, 2024)

Investigating the Relationship Between Intuitive Eating and Eating Disorder/disordered Eating Risk in Collegiate Athletes - N. Randolph; S. Beaty; W. Nguyen; N. Grevstad; P. Sandha; M. Masters; E. Murray (Journal of the Academy of Nutrition and Dietetics, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biogeographic mechanisms involved in the colonization of Madagascar by African vertebrates: Rifting, rafting and runways - Judith C. Masters; Fabien Génin; Yurui Zhang; Romain Pellen; Thierry Huck; Paul P. A. Mazza; Marina Rabineau; Moctar Doucouré; Daniel Aslanian (Journal of Biogeography, 2021)
Aim For 80 years, popular opinion has held that most of Madagascar's terrestrial vertebrates arrived from Africa by transoceanic dispersal (i.e. rafting or swimming). We reviewed this proposition, focussing on three ad hoc hypotheses proposed to render this unlikely scenario more feasible: (a) Could hibernation have helped mammals to reach Madagascar? (b) Could the aquatic abilities of hippopotamuses have enabled them to swim the Mozambique Channel? (c) How valid is the Ali‐Huber model predicting that eastward Palaeogene surface currents allowed rafts to reach Madagascar in 3–4 weeks? Finally, we explored the alternative hypothesis of geodispersal via short‐lived land bridges between Africa and Madagascar. Location East Africa, Madagascar, Mozambique Channel. Taxa Fish, amphibians, reptiles, birds, mammals. Methods We established colonization timeframes using molecular divergence dates estimated for Malagasy vertebrate lineages. We reviewed the likelihood of the “torpid waif” and “swimming hippopotamus” hypotheses, and re‐investigated Ali and Huber's model of Eocene jet‐like currents by tracking particle trajectories in currents simulated using the Institut Pierre‐Simon Laplace Earth System Model. Finally, we summarized recent geological findings from the Mozambique Channel, and used them to compile palaeosedimentological maps using PLACA4D. Results Madagascar's vertebrate fauna has complex origins. Hibernation is probably an adaptation to Madagascar's hypervariable climate, rather than a facilitator of mammal dispersal. Hippopotamus physiology precludes the ability to cross an oceanic channel deeper than 4 m and hundreds of km wide. The Ali‐Huber model of Palaeogene currents considerably underestimated the time required to cross the Mozambique Channel under simulated palaeogeographic conditions. New geological data indicate the existence of three short‐lived land bridges between Africa and Madagascar at 66–60 Ma, 36–30 Ma and 12–05 Ma. Main conclusion The three Cenozoic land bridges afford a more grounded hypothesis for the dispersal of Madagascar's extant biota than transoceanic rafting or swimming, although vicariance, island hopping and limited rafting also played a role.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Neonatal body condition, immune responsiveness, and hematocrit predict longevity in a wild bird population - E. Keith Bowers; Christine J. Hodges; Anna M. Forsman; Laura A. Vogel; Brian S. Masters; Bonnie G. P. Johnson; L. Scott Johnson; Charles F. Thompson; Scott K. Sakaluk (Ecology, 2014)
Measures of body condition, immune function, and hematological health are widely used in ecological studies of vertebrate populations, predicated on the assumption that these traits are linked to fitness. However, compelling evidence that these traits actually predict long‐term survival and reproductive success among individuals in the wild is lacking. Here, we show that body condition (i.e., size‐adjusted body mass) and cutaneous immune responsiveness to phytohemagglutinin (PHA) injection among neonates positively predict recruitment and subsequent longevity in a wild, migratory population of House Wrens ( Troglodytes aedon ). However, neonates with intermediate hematocrit had the highest recruitment and longevity. Neonates with the highest PHA responsiveness and intermediate hematocrit prior to independence eventually produced the most offspring during their lifetime breeding on the study site. Importantly, the effects of PHA responsiveness and hematocrit were revealed while controlling for variation in body condition, sex, and environmental variation. Thus, our data demonstrate that body condition, cutaneous immune responsiveness, and hematocrit as a neonate are associated with individual fitness. Although hematocrit's effect is more complex than traditionally thought, our results suggest a previously underappreciated role for this trait in influencing survival in the wild.

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Herbicides for Establishing Switchgrass in the Central and Northern Great Plains - Robert B. Mitchell; Kenneth P. Vogel; John Berdahl; Robert A. Masters (BioEnergy Research, 2010)

Incorporating Uncertainty into Management Models for Marine Mammals - Barbara L. Taylor; Paul R. Wade; Douglas P. De Master; Jay Barlow (Conservation Biology, 2000)
Good management models and good models for understanding biology differ in basic philosophy. Management models must facilitate management decisions despite large amounts of uncertainty about the managed populations. Such models must be based on parameters that can be estimated readily, must explicitly account for uncertainty, and should be simple to understand and implement. In contrast, biological models are designed to elucidate the workings of biology and should not be constrained by management concerns. We illustrate the need to incorporate uncertainty in management models by reviewing the inadequacy of using standard biological models to manage marine mammals in the United States. Past management was based on a simple model that, although it may have represented population dynamics adequately, failed as a management tool because the parameter that triggered management action was extremely difficult to estimate for the majority of populations. Uncertainty in parameter estimation resulted in few conservation actions. We describe a recently adopted management scheme that incorporates uncertainty and its resulting implementation. The approach used in this simple management scheme, which was tested by using simulation models, incorporates uncertainty and mandates monitoring abundance and human‐caused mortality. Although the entire scheme may be suitable for application to some terrestrial and marine problems, two features are broadly applicable: the incorporation of uncertainty through simulations of management and the use of quantitative management criteria to translate verbal objectives into levels of acceptable risk.

Morphological Correlates of Speciation in Bush Babies - Judith C. Masters; Nigel P. Bragg (International Journal of Primatology, 2000)

Mitochondrial Sequences as Indicators of Genetic Classification in Bush Babies - M. DelPero; J. C. Masters; D. Zuccon; P. Cervella; S. Crovella; G. Ardito (International Journal of Primatology, 2000)

Direct and indirect effects of climate change on St John's wort, Hypericum perforatum L. (Hypericaceae) - Laurel R. Fox; Sérvio P. Ribeiro; Valerie K. Brown; Gregory J. Masters; Ian P. Clarke (Oecologia, 1999)

Plant community dynamics in a calcareous grassland under climate change manipulations - Marcelo Sternberg; Valerie K. Brown; Gregory J. Masters; Ian P. Clarke (Plant Ecology, 1999)

Threats to Imperiled Freshwater Fauna - Brian D. Richter; David P. Braun; Michael A. Mendelson; Lawrence L. Master (Conservation Biology, 1997)
Threats to imperiled freshwater fauna in the U.S. were assessed through an experts survey addressing anthropogenic stressors and their sources. Specifically, causes of historic declines and current limits to recovery were identified for 135 imperiled freshwater species of fishes, crayfishes, dragonflies and damselflies, mussels, and amphibians. The survey was designed to identify threats with sufficient specificity to inform resource managers and regulators faced with translating information about predominant biological threats into specific, responsive actions. The findings point to altered sediment loads and nutrient inputs from agricultural nonpoint pollution; interference from exotic species; and altered hydrologic regimes associated with impoundment operations as the three leading threats nationwide, accompanied by many lesser but still significant threats. Variations in threats among regions and among taxa were also evident. Eastern species are most commonly affected by altered sediment loads from agricultural activities, whereas exotic species, habitat removal/damage, and altered hydrologic regimes predominate in the West. Altered sediment loading from agricultural activities and exotic species are dominant problems for both eastern mussels and fishes. However, eastern fishes also appear to be suffering from municipal nonpoint pollution (nutrients and sediments), whereas eastern mussels appear to be more severely affected by altered nutrient impacts from hydroelectric impoundments and agricultural runoff. Our findings suggest that control of nonpoint source pollution associated with agriculture activities should be a very high priority for agricultural producers and governmental support programs. Additonally, the large number of hydropower dams in the U.S. subject to federal re‐licensing in coming years suggests a significant opportunity to restore natural hydrologic regimes in the affected rivers.

Relationships between NADPH diaphorase staining and neuronal, endothelial, and inducible nitric oxide synthase and cytochrome P450 reductase immunoreactivities in guinea-pig tissues - H. M. Young; Anna J. O'Brien; John B. Furness; Daniela Ciampoli; James P. Hardwick; Timothy J. McCabe; Ramani Narayanasami; Bettie Sue S. Masters; W. Ross Tracey (Histochemistry and Cell Biology, 1997)

Localization of an RNA-binding domain in the nucleocapsid protein of the coronavirus mouse hepatitis virus - P. S. Masters (Archives of Virology, 1992)